2017
DOI: 10.2166/wh.2017.080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pathogenic bacterial activity on growth of Scenedesmus sp. and removal of nutrients from public market wastewater

Abstract: The present study aims to investigate the influence of Staphylococcus aureus, Escherichia coli and Enterococcus faecalis in public market wastewater on the removal of nutrients in terms of ammonium (NH) and orthophosphate (PO) using Scenedesmus sp. The removal rates of NH and orthophosphate PO and batch kinetic coefficient of Scenedesmus sp. were investigated. The phycoremediation process was carried out at ambient temperature for 6 days. The results revealed that the pathogenic bacteria exhibited survival pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The uptake of Ni by killed bacterial cells was also investigated in the study, where it was observed that the killed cells were not able to uptake Ni from the medium, but adsorption was reported due to the availability of biosorbent sites that adsorb Ni from the environment without the aid of a specific uptake system (Figure 5). Previous researchers have also reported on the biosorption ability of bacterial killed biomass [47,48]. The pilot-scale study was also conducted to determine the Ni removal efficacy of B. altitudinis, indicating it to be an effective agent of Ni bioremediation, as it was able to remove remarkable quantities of Ni (Figure 6), which was also reported by Rivas-Castillo et al [49].…”
Section: Discussionsupporting
confidence: 63%
“…The uptake of Ni by killed bacterial cells was also investigated in the study, where it was observed that the killed cells were not able to uptake Ni from the medium, but adsorption was reported due to the availability of biosorbent sites that adsorb Ni from the environment without the aid of a specific uptake system (Figure 5). Previous researchers have also reported on the biosorption ability of bacterial killed biomass [47,48]. The pilot-scale study was also conducted to determine the Ni removal efficacy of B. altitudinis, indicating it to be an effective agent of Ni bioremediation, as it was able to remove remarkable quantities of Ni (Figure 6), which was also reported by Rivas-Castillo et al [49].…”
Section: Discussionsupporting
confidence: 63%
“…For example, Staphylococcus aureus, Escherichia coli, and Enterococcus faecalis were reduced by 3-4 log in cultures of the microalga Scenedesmus sp. (Al-Gheethi et al, 2017). It is unclear, however, if such reduction was attained through pathogen death, inactivation, or is an artefact of the testing procedure.…”
Section: Contamination Potential Of Produced Biomass With Pathogens Mmentioning
confidence: 99%
“…However, in developing countries such as Yemen, all wastewater from different industries is typically collected by a single sewage treatment plant. This can lead to an overload of the plant's capacity, potentially compromising its effectiveness and resulting in lower-quality treated effluents [16][17][18][19]. Due to centralized systems' high capital and operational costs, decentralized systems appear vital, cost-effective, reliable, and environmentally sustainable, especially for developed countries that cannot afford these massive expenses [20,21].…”
Section: Introductionmentioning
confidence: 99%